Annual Plan West Bengal 2001-2002 - Planning Commission (Planning Commission, 2001)
The State Govt. considers universalisation of Primary Education to be the most important component of Human Resource Development and has, therefore, set a target of 5 years to have it achieved. Improvement of the quality of Higher’ Education and percolation of the benefits of scientific research and development to the masses are our major areas of importance; It shall, therefore, be our endeavours to forge a linkage between the advancement of Higher Education and industrial and agricultural development. Network of Technical Education over the last few years has been strengthened significantly, with the addition to the number of Polytechnics, I.T.I.s and vocational training centres. The State, Govt, shall, endeavour to further expand the benefits of technical education with emphasis on modern, and contemporary disciplines suited to the felt needs of the State and its people. This is aimed at lasting benefits of the society.
Development and Planning Department, Government of West Bengal
Government of West Bengal